2024
DOI: 10.1002/pul2.12356
|View full text |Cite
|
Sign up to set email alerts
|

Plasma NEDD9 is increased following SARS‐CoV‐2 infection and associates with indices of pulmonary vascular dysfunction

George A. Alba,
Iris Y. Zhou,
Molly Mascia
et al.

Abstract: Compared to healthy volunteers, participants with post‐acute sequelae of SARS‐CoV‐2 infection (PASC) demonstrated increased plasma levels of the prothrombotic protein NEDD9, which associated inversely with indices of pulmonary vascular function. This suggests persistent pulmonary vascular dysfunction may play a role in the pathobiology of PASC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Regarding the pulmonary vascular bed, Zhou et al demonstrated reduced pulmonary microvascular perfusion in 10 COVID-19 patients (8 months after infection) compared to age-matched healthy volunteers using dynamic performed contrast-enhanced magnetic resonance imaging (DCE-MRI) [139]. Interestingly, as in PAH [140], increased plasmatic levels of the prothrombotic protein NEDD9 have been described in these patients, reflecting pulmonary endothelial dysfunction [141].…”
Section: Persistent Vascular Endothelial Dysfunctionmentioning
confidence: 99%
“…Regarding the pulmonary vascular bed, Zhou et al demonstrated reduced pulmonary microvascular perfusion in 10 COVID-19 patients (8 months after infection) compared to age-matched healthy volunteers using dynamic performed contrast-enhanced magnetic resonance imaging (DCE-MRI) [139]. Interestingly, as in PAH [140], increased plasmatic levels of the prothrombotic protein NEDD9 have been described in these patients, reflecting pulmonary endothelial dysfunction [141].…”
Section: Persistent Vascular Endothelial Dysfunctionmentioning
confidence: 99%